2016
DOI: 10.1088/0268-1242/31/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of p-type Na-doped Cu2O by electrodeposition for a p-n homojunction thin film solar cell

Abstract: In this work, a method of enhancing the electrical properties of the electrodeposited p-type Cu 2 O film is described. Sodium doped Cu 2 O was achieved by adding sodium aluminate complex solution to the electrodeposition alkaline Cu (II) lactate electrolyte. The optimal Na content [Na at% atomic ratio] incorporated in the Cu 2 O film was found to be approximately 1.34 at.%. The XPS result shows that the binding energy at 1072.4±0.2 eV corresponds to the presence of sodium in sodium oxide. The optimized resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The doping of Cu 2 O by Na does not change the nature of his conductivity; the calculated energy of the gap is 0.35 eV. Elfadill et al [47] showed that Na doping Cu 2 O is a p-type characteristic, which shows that our calculations are in good agreement with experimental data. In addition, Minami et al used Cu 2 O doped Na as p-type in p-n heterojunction and/or homojunction solar cells [48,49].…”
Section: Na and H Doped Cu 2 Osupporting
confidence: 81%
“…The doping of Cu 2 O by Na does not change the nature of his conductivity; the calculated energy of the gap is 0.35 eV. Elfadill et al [47] showed that Na doping Cu 2 O is a p-type characteristic, which shows that our calculations are in good agreement with experimental data. In addition, Minami et al used Cu 2 O doped Na as p-type in p-n heterojunction and/or homojunction solar cells [48,49].…”
Section: Na and H Doped Cu 2 Osupporting
confidence: 81%
“…[ 28 ] Rather, instability issues and challenges of fabricating doped Cu 2 O absorber layers are considered as some major drawbacks of employing this material as prospect layer in all‐oxide heterojunction PVs. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…[28] Rather, instability issues and challenges of fabricating doped Cu 2 O absorber layers are considered as some major drawbacks of employing this material as prospect layer in all-oxide heterojunction PVs. [29] Unlike commonly investigated p-on-n architectures (ntype being the front illuminated contact) of MOx PVs, the inverted structures (n-on-p) of these systems remained unattainable due to technical obstacles for synthesizing a MOx p-type layer, which can enable efficient light absorption in a relatively thin thickness, and at the same time delivers enhanced photocurrent. However, a quintessential inverted structure of MOx heterojunction, with p-type illumination window can enable generation of more acceptors and consequently result in higher carrier separation at the p-n junction interface (Figure 1B).…”
mentioning
confidence: 99%
“…1,2 The resistivity of this semiconductor, when prepared by electrodeposition, can vary in the range of 10 1 to 10 11 X cm depending on the deposition parameters and incorporation of dopants. [3][4][5][6][7][8] Cu 2 O is a relevant material for several applications such as photocatalysis 9 and solar cells (see Refs. 10 and 11, and therein), and it is very important to develop doping processes to reduce the resistivity and control the n and p character of the material.…”
Section: Introductionmentioning
confidence: 99%